Blind Alleys in the Controversy over the Paul of History - Seifrid, Mark A. 1953- (1994)
E.P. Sanders’ reading of Paul against the backdrop of ‘covenantal nomism’ is badly flawed, since it obscures Paul’s coming to understand the cross as working the justification of the ungodly. Two important extensions of Sanders’ paradigm also fail to illumine Paul in his context. ‘Works of the Law’ are not simply ethnic boundaries, as J.D.G. Dunn claims, but marks of piety as well. N.T. Wright’s proposal that Christ provided the solution to Paul’s experience of exile reverses the manner in which exilic language appears in Paul’s letters. Contrary to the common assumption, Luther’s theology of the cross and justification is not barren or irrelevant, and more closely accords with Paul than recent attempts to understand him.
Keywords: new perspective on paul; Works Of The Law; covenantal nomism; e. p. sanders; paul; New Testament